Investigating Risk Effect and Profit Management on Bank Credit Risk - Farhadvand, Seyedeh Mahtab; Jalilian, Omid (International Journal of Economics and Financial Issues, 2017)
The aim of this research is to investigate risk effect and profit management on bank credit risk. The research population are the accepted banks in Tehran Stock Exchange during one quinquennial from 2010 to 2014. Finally, 18 corporations information were gathered based on the research limitations by systematic deletion method. The research is an applicational one in term of its aim, is post eventual based on the historical information and its deductive methodology is apriority and correlative. The research includes four main hypotheses and two subordinate hypotheses. To investigate research hypotheses, linear regression and correlation are used. Moreover, Eviews software is used to analyze research data and hypotheses. After designing of the research hypotheses in division of each hypothesis, these conclusions have received. Bank risk and profit management have positive meaningful effect on credit risk. In addition there is a positive meaningful relationship between corporation risk and profit management. Although, there is no positive meaningful effect between bank credit and profit management on credit risk. Keywords: credit risk, profit management, commercial banks risks JEL Classifications: C32; O13; O47